The Cortisol to Cortisone Ratio during Cardiac Catheterisation in Sows - Hana Skarlandtová (Prague Medical Report, 2015)
A possible effect of mini-invasive heart intervention on a response of hypothalamo-pituitary-adrenal stress axis and conversion of cortisone to cortisol were studied. We have analysed two stress markers levels (cortisol, cortisone) and cortisol/cortisone ratio in 25 sows using minimally invasive heart catheterisation as the stress factor. The values of studied parameters were assessed in four periods of the experiment: (1) the baseline level on the day before intervention, (2) after the introduction of anaesthesia, (3) after conducting tissue stimulation or ablation, and (4) after the end of the catheterisation. For statistical analyses we used the non-parametric Friedman test for four dependent samples (including all four stages of the operation) or three dependent samples (influence of operation only, baseline level was excluded). Statistically significant differences in both Friedman tests were found for cortisol and for cortisone. We have found the highest level of cortisol/cortisone ratio in unstressed conditions, then it decreased to the minimal level at the end of the intervention. We have concluded that cortisol levels are blunted by the influence of anaesthesia after its administration, and therefore decrease back to the baseline at the end of the operation.